Cell Density- and Quorum Sensing-Dependent Expression of Type VI Secretion System 2 in Vibrio parahaemolyticus - Wang, Li (Public Library of Science, 2013)

(untitled)
BACKGROUND: Vibrio parahaemolyticus AphA and OpaR are the two master quorum sensing (QS) regulators that are abundantly expressed at low cell density (LCD) and high cell density (HCD), respectively, with a feature of reciprocally gradient production of them with transition between LCD and HCD. The type VI secretion system 2 (T6SS2) gene cluster can be assigned into three putative operons, namely VPA1027-1024, VPA1043-1028, and VPA1044-1046. T6SS2 contributes to adhesion of V. parahaemolyticus to host cells. METHODOLOGY/PRINCIPAL FINDINGS: OpaR box-like sequences were found within the upstream promoter regions of all the above three operons, while none of AphA box-like elements could be identified for them. The subsequent primer extension, LacZ fusion, electrophoretic mobility shift, and DNase I footprinting assays disclosed that OpaR bound to the promoter regions of these three operons to stimulate their transcription, while AphA negatively regulated their transcription most likely through acting on OpaR. This regulation led to a gradient increase of T6SS2 transcription with transition from LCD to HCD. CONCLUSIONS/SIGNIFICANCE: V. parahaemolyticus OpaR and AphA positively and negatively regulate T6SS2 expression, respectively, leading to a gradient elevation of T6SS2 expression with transition from LCD to HCD. T6SS2 genes are thus assigned as the QS regulon members in V. parahaemolyticus.